Posterior Indirect Adhesive Restorations and Preparation Designs - Arife Doğan; Zeynep Söylemez (Current Research in Dental Sciences)
The main goal of restorative dentistry is to preserve healthy dental tissues. "Posterior indirect adhesive restorations" have an important role in restoring the anatomical form, aesthetics and function of tooth tissue losses in the posterior region. These restorations aim to restore lost dental tissues as a result of caries, erosion and/or abrasion and to support healthy tissues. Posterior indirect adhesive restorations have become more effective with the development of computer-aided design/computer-aided manufacturing (CAD/CAM) systems. These methods work in line with the principles of biomimetic dentistry, aiming to return dental tissues to their full function and provide stability.One of the important factors to consider in such restorations is to keep the amount of preparation as minimal as possible. This factor, which is of critical importance for the long-term success of restorations, is also effective in obtaining optimal results. Preserving intact enamel and dentin tissues during preparation and increasing the surface area instead of preparation in line with retention principles affects the quality of the adhesive bond and can increase the durability of the restoration. As a result, posterior indirect adhesive restorations are a much more minimally invasive treatment option compared to conventional treatments to achieve aesthetic, functional and biological results.The purpose of this article is to give general information about posterior indirect adhesive restorations and preparation designs.